1994
DOI: 10.1128/iai.62.3.1015-1025.1994
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the Treponema pallidum tpn50 gene, an ompA homolog

Abstract: Treponema paUlidum is a pathogenic spirochete that has no known genetic exchange mechanisms. In order to identify treponemal genes encoding surface and secreted proteins, we carried out TnphoA mutagenesis of a T. paUlidum genomic DNA library in Escherichia coli. Several of the resulting clones expressed enzymatically active T. pallidum-alkaline phosphatase fusion proteins. The DNA sequence of the 5' portion of a number of the treponemal genes was obtained and analyzed. A recombinant clone harboring plasmid p4A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 80 publications
0
25
0
Order By: Relevance
“…The complete sequence lor tpn50 was obtained from two genomic clones wifh overlapping inserts. Except tor minor discrepancies (absence of nucleotides 409-411, substitution of G for C at nucleotide 1014, and substitution ot A for C at nucleotide 1082 (data not shown), the nucleotide and amino acid sequences were identical to those pLiblished by Hardham and Stamm (1994). De Mot and Vanderieyden {1994) recently identified a group of 28 peptidoglycan-associated membrane proteins from diverse bacterial species with extended homology to the C-terminus of Pseudomonas fluorescens OprF; thts group inciudes all of (he polypeptides reported to be homologous to TpNSO (Hardham and Stamm, 1994).…”
Section: (Molecular Analysis and Localization Of Tpnsomentioning
confidence: 69%
See 4 more Smart Citations
“…The complete sequence lor tpn50 was obtained from two genomic clones wifh overlapping inserts. Except tor minor discrepancies (absence of nucleotides 409-411, substitution of G for C at nucleotide 1014, and substitution ot A for C at nucleotide 1082 (data not shown), the nucleotide and amino acid sequences were identical to those pLiblished by Hardham and Stamm (1994). De Mot and Vanderieyden {1994) recently identified a group of 28 peptidoglycan-associated membrane proteins from diverse bacterial species with extended homology to the C-terminus of Pseudomonas fluorescens OprF; thts group inciudes all of (he polypeptides reported to be homologous to TpNSO (Hardham and Stamm, 1994).…”
Section: (Molecular Analysis and Localization Of Tpnsomentioning
confidence: 69%
“…Except tor minor discrepancies (absence of nucleotides 409-411, substitution of G for C at nucleotide 1014, and substitution ot A for C at nucleotide 1082 (data not shown), the nucleotide and amino acid sequences were identical to those pLiblished by Hardham and Stamm (1994). De Mot and Vanderieyden {1994) recently identified a group of 28 peptidoglycan-associated membrane proteins from diverse bacterial species with extended homology to the C-terminus of Pseudomonas fluorescens OprF; thts group inciudes all of (he polypeptides reported to be homologous to TpNSO (Hardham and Stamm, 1994). Computer-based sequence alignments revealed that the C-terminal third of TpN50 has homology with three psptidoglycan-associated proteins of Gram-positive bacteria (i.e.. Bacillus subtilis MofB, B. subtilis OrfB, and BaciHus megaterium OrfB) as well as those of Gram-negative bacteria {data not shown).…”
Section: (Molecular Analysis and Localization Of Tpnsomentioning
confidence: 69%
See 3 more Smart Citations